Asālīb Al-Balāghiyyah Wa Ma’ānīhā Fī Surati-l-Fath - Muhammad Wahyudi; Abeer Heider; Anita Nurjanah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
A Muslim should firmly hold Qur’an and Sunnah at all times in their lives and understanding them is a must. Qur'an has many verses explaining aqeedah and theology, Muslims dedicatedly learn it to limit the error and mistaken things on the content. Meanwhile, in the Qur’an Balaghah idioms are detailly characteristics with high vocabulary enrichment, even Uslub Ilmi or Uslub Adabi. Thus, researchers employe to conduct research Tahlilu-l-Asalib Al-Balaghiyyah Fi Surati-l-Fath as an object that has many idioms describing maghfiroh of Allah, Muslimin Independence on unbelievers, socialization, attitude, ibadah, and advice. Understanding Alqur’an with the Arabic Language needs comprehensive learning, and understanding the Arabic Language itself needs three bits of knowledge; Nahwu, Sharaf, and Balaghah. The researchers limit  Balaghah as a focused matter; it delineates idioms. Qur'an consists of many idioms that must be understood well by a Muslim who expects to master Alqur’an. Based on the aforementioned last point, the researchers apply a qualitative method to reach the goals. The data is collected by books and documentation to investigate the finding. The result of the finding many Uslub in there, they are Al-Isti’arah Almakniyah, Isti’arah Tashrihiyah, Tasybih Tamtsili, Kinayah, Iltifat, Ithnab, Shiyagul Mubalaghah, Iijazul Qashri, Thibaqu Iijabi, Thibaqu Sulbi, Saja’ dan Muqabalah. For the meaning in it, they are Al-Mubaya’ah, Al-mubadalah, Ad-diin, Atta’dziim, Aliltifat, Attakriir, Almubalaghah, Attasyriif, Attarghiib, Attadhad, Attashdiiq dan Almuqabalah. To develop the current issues within this research, the researchers suggest to the further scholars to find out the other sides of the chapter such as use of Balaghah in idioms of Surah al-Fath and some other uniques within this surah.